Study of clinical, imaging and pathological assessment of breast lumps: an observational study - Laul, Sumedha; Saxena, Divish; Wasnik, Nitin (International Surgery Journal, 2020)
Background: A palpable lump in a woman’s breast could be benign or malignant and it requires prompt evaluation to confirm or exclude cancer. This study aims to establish the correlation between clinical and radiological parameters for provisional diagnosis of breast lumps and the role of histopathology for final diagnosis of these breast lumps. Methods: Total 275 female patients with palpable breast lumps were included in the study, where a detailed history was recorded and clinical examination was done. All patients underwent ultrasonography of the breast along with fine needle aspiration cytology or histopathology, wherever indicated. Results: Benign breast lumps were found more commonly in 18-30 years of age group whereas malignant breast lumps were seen more commonly in the 41-60 years age group and the incidence increased with age. Fixity to skin was present in 5.1% and fixity to chest wall was present in 5.8% respectively, and all of these cases turned out to be malignant. Conclusions: Attributing factors for suspicion of malignant lumps are advanced age, fixity to surrounding structures, presence of ulceration and peau’d orange breast skin appearance. Although for confirmation of malignancy from a suspected breast lump requires either cytology or histopathology of the excised specimen.